Developing an economic partnership framework between the Lheidli T'enneh First Nation and Initiatives Prince George Development Corporation - Petrucci, Franca (Author); Tallman, Rick (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2009)
Successful partnerships balance corporate, social and environmental responsibility, and ensure prosperity for both partners. The most effective type is a collaborative partnership, which exhibits mutuality, equal power in the decision-making process, and resource-sharing. For First Nations, a partnership with a business can contribute to a future that involves them in a mutually respectful manner by incorporating their values and principles. This facilitates First Nations participation in and contribution to a vibrant and strong economy. For businesses, a partnership with a First Nation can result in access to the rapidly growing pool of natural and financial resources currently under the control of First Nation peoples. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1600517